2015
DOI: 10.1039/c5nj01640a
|View full text |Cite
|
Sign up to set email alerts
|

In situ thermal synthesis of novel polyimide nanocomposite films containing organo-modified layered double hydroxide: morphological, thermal and mechanical properties

Abstract: An organic-inorganic hybrid compound constituted by a Zn/Al layered double hydroxide (LDH) intercalated with citric acid (LDH-CA), was dispersed in polyimides (PIs) with N-benzonitrile side group, through in situ polymerization. At first, 3-(bis(4-aminophenyl)amino)benzonitrile as a diamine monomer was synthesis and then it was reacted with 4,4′-benzophenone tetracarboxylicdianhydride via thermal imidization method to formed prossable PI. To improve the thermal and mechanical properties and also to avoid th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…The incorporated anions and water between the layers and various metal cations (M 2+ / 3+ ) results in a larger interlayer space and unique redox characteristics in LDHs, respectively, providing a notable electrochemical performance 2022. Recent studies have been shown that LDHs are electrocatalytically active and offer superb a high stability for long‐term employment 23–25.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporated anions and water between the layers and various metal cations (M 2+ / 3+ ) results in a larger interlayer space and unique redox characteristics in LDHs, respectively, providing a notable electrochemical performance 2022. Recent studies have been shown that LDHs are electrocatalytically active and offer superb a high stability for long‐term employment 23–25.…”
Section: Introductionmentioning
confidence: 99%
“…In the spectra of the PI, absorption bands of the imide groups appeared at 1774 and 1718 cm −1 for the antisymmetric and symmetric stretching vibrations of the carbonyl groups. 41 The bands around 1374 and 816 cm −1 were ascribed to the stretching and bending vibrations of C–N–C in the imide ring (Figure 2(b)).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, synthesis of PIs containing such functional groups along their main chains or within their side chains is the most frequently used method to tailor their properties. Moreover, introduction of nanoparticles and preparation of related nanocomposites would further improve their properties . As it has been widely proved, the presence of some types of nanoparticle or nanofiber in PI and PI copolymer matrices results in improved thermo‐mechanical and physical properties of polymers without deteriorating their desirable intrinsic features …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, introduction of nanoparticles and preparation of related nanocomposites would further improve their properties. [11][12][13] As it has been widely proved, the presence of some types of nanoparticle or nanofiber in PI and PI copolymer matrices results in improved thermo-mechanical and physical properties of polymers without deteriorating their desirable intrinsic features. [14][15][16] Sepiolite (Sep) is a hydrated magnesium silicate having the half-unit cell chemical formula of Mg 8 Si 12 O 30 (OH) 4 .12H 2 O.…”
Section: Introductionmentioning
confidence: 99%